Appraisal Evaluation Tool for College Staff - Brindha, N; Dhivya, P (International Journal of Computer Sciences and Engineering, 2025)
Appraisal is an expert estimate of the value of something. Staff appraisal can be tricky. If you get this wrong, you will negatively impact your staff. This intranet web application will provide the feasible solution to boost the production of each of your staffs, regardless of their current achievement level. An effective staff appraisal system ought to validate by the students of the department. This aspect of the performance appraisal process will begin anew unless the employee is scheduled to participate in the Supervisory Performance Appraisal process or the process is warranted as a result of the Performance Growth Plan, or the staff’s job description has changed significantly. The evaluation cycle outlined below provides the employer with the opportunity to assess and evaluate the performance of the teacher on the district-adopted teacher performance evaluation criteria. Throughout the course of the evaluation cycle, strengths and areas of growth will be identified and communicated to staff. The assessment tool used for staff contains criteria like specific behaviours, knowledge, presentation skills that pertain to all staff. It is assumed that all staffs of the college are professional and, as such, will perform duties with integrity, and maintain a positive, vigilant attitude toward student physical safety and emotional well being.